A Comparative Study of the Impact of Leader-member Exchange in Two Samples: U.S.A. And Poland - Grodzicki, Jacek; Varma, Arup (Organizations and Markets in Emerging Economies, 2011)
Leader-Member Exchange (LMX) theory argues that supervisor-subordinate interactions in the workplace are guided by the type of relationship that develops in each individual dyad, and that the quality of the relationship significantly impacts critical outcomes such as performance ratings. Further, it has been argued that supervisors and subordinates often view the relationship through different lenses – leading to significantly different perceptions of the quality of relationship. In this field study, using data from 32 supervisors and 104 subordinates in the US, and 72 supervisors and 116 subordinates in Poland, we examine the relationship between LMX and performance ratings, as well as compare supervisor and subordinate perceptions of the relationship. In both samples, supervisor ratings of LMX quality were higher than those of the subordinates, and subordinates who received higher LMX ratings from their supervisors also received higher performance ratings. Finally, the correlation between supervisor and subordinate ratings of LMX was significantly higher for the Polish sample as compared to the US sample. We discuss the results in terms of both theoretical and practical significance, and offer suggestions for future research.
Keywords: LMX; supervisor-subordinate relationships; performance ratings; Poland; US